Incidence and prognosis of crown discoloration in traumatized primary teeth: A retrospective cohort study. Issue 4 (8th March 2020) - Goettems, Marília Leão; Thurow, Luiza Beatriz; Noronha, Thaís Gioda; da Silva Júnior, Ivam Freire; Kramer, Paulo Floriani; Feldens, Carlos Alberto; da Costa, Vanessa Polina Pereira
Abstract: Background/Aim: Knowledge of factors influencing the occurrence of crown discoloration following traumatic dental injuries in primary teeth and understanding its possible consequences can help dentists to provide appropriate care. The aim of this retrospective cohort study was to investigate the incidence of crown discoloration following trauma in primary teeth. This study also estimated the risk of pulp necrosis with subsequent infection of the root canal system and pulp canal obliteration in discolored teeth. Material and Methods: Records of children treated at the specialized trauma center of the Federal University of Pelotas during a period of 10 years were analyzed. Patient details including the type of injury, presence of crown discoloration, pulp necrosis, and pulp canal obliteration were collected. Photographs of teeth with crown discoloration were assessed to evaluate the color presented (yellow or dark). Chi‐square tests and Poisson regression were used for data analyses ( P  < .05). Results: A total of 355 children with 628 traumatized teeth were included in the study. The incidence of crown discoloration was 27.9%, and 20.5% of the teeth were affected. Discoloration was higher in children whose age at the time of trauma was 2‐4 years ( P  = .020), and it was associated with the type of injury ( P  = .019). Discolored teeth had a twofold risk of pulp necrosis and subsequent infection of the root canal system (RR 1.98 95% CI 1.42‐276; P  < .001) and a higher risk of pulp canal obliteration (RR 8.47; 95% CI 4.95‐14.51; P  < .001) than did teeth without discoloration. Teeth with dark and yellow discoloration were significantly associated with pulp necrosis and pulp canal obliteration, respectively ( P  < .001). Conclusions: This study demonstrates the importance of monitoring traumatized primary teeth with crown discoloration, particularly those appearing darker, owing to their higher risk of pulp necrosis and subsequent infection of the root canal system.